Horn of plenty : Sixteen artist from NYC - Beeren, W.A.L.; Cameron, Dan; Oosterhof, Gosse (Amsterdam : Stedelijk Museum Amsterdam, 1989)
Bickerton, Ashley ; Doran, Anne ; Dunham, Carroll ; Eckart, Christian ; Ericson, Kate ; Gober, Robert ; Halley, Peter ; Kessler, Jon ; Koons, Jeff ; Lasker, Jonathan ; Prince, Richard ; Rollins, Tim & K.O.S. ; Saint Clair, Cemin ; Steinbach, Haim ; Wool, Christopher ; Yarber, Robert ; Ziegler, Mel
biog., tent. p. 94-103
Horn of Plenty / Hoorn van overvloed, Stedelijk Museum Amsterdam, 14.1. - 19.2.1989
Nederlands & Engels
boek
Keywords: New York; U.S.A.